2009
DOI: 10.1016/j.nucmedbio.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18 labeling and biodistribution studies on peroxisome proliferator-activated receptor-γ ligands: potential positron emission tomography imaging agents

Abstract: Introduction The peroxisome proliferator-activated receptor gamma (PPARγ) is an important regulator of lipid metabolism; it controls the differentiation of pre-adipocytes and is also found at high levels in small metastatic tumors. In this report, we describe the radiochemical synthesis and evaluation of two 18F-labeled analogs of the potent and selective PPARγ agonist, Farglitazar. Materials and Methods The isomeric aromatic fluorine-substituted target compounds ([18F]1 and [18F]2) were prepared in fluorine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The preparation of [ 18 F]fluoroarenes from the reactions of [ 18 F]fluoride ion with diaryliodonium salts (Scheme 1) [9,10] is finding increasing application for preparing labeling synthons [1113] and PET radiotracers [1417]. This radiofluorination method, unlike aromatic nucleophilic substitution ( S N Ar) in non-hypervalent substrates, allows NCA [ 18 F]fluoride ion to be introduced readily into electron-deficient or electron-rich rings, irrespective of ring substituent positions [9,10,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of [ 18 F]fluoroarenes from the reactions of [ 18 F]fluoride ion with diaryliodonium salts (Scheme 1) [9,10] is finding increasing application for preparing labeling synthons [1113] and PET radiotracers [1417]. This radiofluorination method, unlike aromatic nucleophilic substitution ( S N Ar) in non-hypervalent substrates, allows NCA [ 18 F]fluoride ion to be introduced readily into electron-deficient or electron-rich rings, irrespective of ring substituent positions [9,10,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent tissue distribution studies of two fluorine-18 analogs of GI262570 in normal female rats did not demonstrate increased tracer uptake in target tissues, and blocking studies showed little in vivo selectivity. Metabolic stability studies and the low fluoride incorporation into the bone suggested that the compounds were stable [14], and rapid metabolism was not responsible for the low uptake of radiotracers in the target tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These fluorine-18 labeled radiotracers had good potential for PPARγ imaging because of their high subtype specificity (PPARγ/PPARα > 100). However, despite high affinity and good metabolic stability, in vivo studies demonstrated poor uptake in target tissues, which was attributed to their high lipophilicity [14]. …”
Section: Introductionmentioning
confidence: 99%
“…71,72 In particular, the radioligand 42 was prepared by nucleophilic fluorination of phenyliodonium salt 41 in good radiochemical yield (Scheme 20). 71 Interestingly, the reactions of iodonium salts 41 bearing the 3-methoxyphenyl or 2-thienyl substituents instead of the phenyl did not afford any fluorinated product 42.…”
Section: Scheme 19 Synthesis Of Pet Ligand [ 18 F]daa1106 (Compound mentioning
confidence: 99%